"When he divorced my mother, my father divorced me as well.": the relational experiences of women who grew up apart from their fathers - Yıldırım, İrem (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: This thesis aims to explore relational experiences of women who grew up apart from their fathers. Ten heterosexual women (age range: 23-27), who experienced parental divorce before the age of five and who were in a romantic relationship participated in this study. After conducting in-depth interviews and carrying out thematic analysis, four categories were revealed. The first category, father-daughter relationship, includes nine themes: not being close with father, lack of sincerity in father-daughter relationship, rejecting father and being rejected by father, not longing for father, varied contact and communication, limited sharing with father, ineffective conflict resolution, the gap between expectations and reality, and disappointment with unmet expectations. The second category, mother-daughter relationship, involves four themes: feeling close and satisfied with the mother-daughter relationship, empathizing with mother, being able to share with mother, and being able to solve the problems with mother. The third category, parental divorce and separation from the father, consists of eight themes: disclosures about parental divorce, the mediator role of the mother in the father-daughter relationship, alliance with the mother, the effect of observing other family structures, the effect of father absence on childhood experiences, on identity, on others’ negative perceptions of self, and compensating for father absence. The fourth category, experience of romantic relationships, consisted of five themes: feeling close with partner, communication challenges and conflict resolution in romantic relationship, the impact of the father on daughter’s partner preference and on the nature of romantic relationship. Participants described a negative course of father-daughter relationship including low paternal involvement, rare contact frequency and dysfunctional communication patterns. The mother-daughter relationship was described mostly positively. The results show that the father-daughter relationship and father absence affect several issues in adult daughters’ romantic relationships including partner preference, attitudes towards partners, conflict resolution strategies, and the longevity of the relationship. Implications of the results, limitations and suggestions for further studies are discussed in light of existing literature.

ÖZET: Bu çalışma babasından ayrı büyümüş kadınların ilişkisel deneyimlerini incelemeyi amaçlamaktadır. 5 yaşına gelmeden ebeveynleri boşanmış ve şu anda bir romantik ilişki içinde olan 10 heteroseksüel kadın (yaş aralığı: 23-27) çalışmaya katılmıştır. Yarı yapılandırılmış görüşmeler yapıldıktan ve tematik analiz uygulandıktan sonra dört ana kategori ortaya çıkmıştır. I?lk kategori, baba-kız ilişkisi, dokuz tema içermektedir: babaya yakın hissetmemek, baba-kız ilişkisindeki samimiyetsizlik, babayı reddetmek ve baba tarafından reddedilmek, babaya özlem duymamak, değişken iletişim sıklığı ve örüntüsü, babayla kısıtlı paylaşım, işlevsiz çatışma çözümleri, beklentiler ve gerçeklik arasındaki fark, karşılanmayan beklentilere karşı hayal kırıklığı. I?kinci kategori, anne-kız ilişkisi, dört tema içermektedir: anneye yakın hissetmek ve anne-kız ilişkisinden memnun olmak, anneyle empati kurmak, anneyle rahatça paylaşım yapmak, anneyle sorunları çözebilmek. Üçüncü kategori, ebeveyn boşanması ve babadan ayrılık, sekiz tema içermektedir: ebeveyn boşanmasıyla ilgili açıklamalar, annenin baba-kız ilişkisindeki aracı rolü, anneyle birlik olmak, diğer aile dinamiklerini gözlemlemenin etkisi, baba yokluğunun çocukluk deneyimlerine, kişiliğe, diğerlerinin olumsuz algısına etkisi, ve baba yokluğunun telafisi. Dördüncü kategori, romantik ilişki deneyimi, beş tema içermektedir: partnere yakın hissetmek, romantik ilişkide iletişim zorlukları ve çatışma çözümü, babanın kızının partner seçimine ve romantik ilişki dinamiğine etkisi. Genel olarak katılımcılar düşük baba katılımı, seyrek görüşme sıklığı ve işlevsiz iletişim örüntüleri içeren olumsuz bir baba-kız ilişki seyri tanımlamışlardır. Anne-kız ilişkisi genel olarak olumlu şekilde tanımlanmıştır. Sonuçlar baba-kız ilişkisinin ve baba yokluğunun kadınların romantik ilişkilerinde partner tercihi, partnerlerine karşı tutumları, çatışma çözme yöntemleri ve ilişki süresi konularını etkilediğini ortaya koymuştur. Sonuçların sağladığı bilgiler, çalışmadaki kısıtlamalar ve gelecek çalışmalar için öneriler tartışılmıştır.
"Babam annemden boşandığında benden de boşandı.": babasından ayrı büyümüş kadınların ı?lişkisel deneyimleri
Keywords: parental divorce; father absence; father-daughter relationship; mother-daughter relationship; romantic relationship experiences; ebeveyn boşanması; baba yokluğu; baba-kız ilişkisi; anne-kız ilişkisi; romantik ilişki deneyimi